PARTISIPASI PEREMPUAN DALAM PENYUSUNAN RENCANA PEMBANGUNAN DAERAH: (Studi Di Kabupaten Lamandau) - Miari dan Evi Nurleni, Miari dan Evi Nurleni (Jurnal Administrasi Publik (JAP), 2017)
MEA enactedin 2015 aimstocreate the ASEAN asasing lemarketandproductionbase unity. The number of unemployed in the District Lamandau recorded has included women. With the AEC 2015 will open up opportunities for participation of women. In Musrenbang, women’svotemustberepresentedasaformofgenderequality.BasedonthetheoryofGAD (Gender And Development) is the empowermentapproach. This study used a qualitative methodology to explore more in depth information. With the object of research in Musrenbang conducted by Bukit Desa Jaya and the District SematuJaya,whichisintheDistrictLamandau.Interviewswereconductedwithafocuson the principles of participation and factors affecting women’s participation. As well as this research uses an interactive model of data analysis. Women’sparticipationinMusrenbangstillminimal.EvenateverylevelMusrenbang, the fewer female portion. Women’s participation is minimal, because there are factors that impede. That is one of the strategic position or positions of women in governance. Such as mayor or as Chairman of the Development of Family Welfare(PKK)